2020
DOI: 10.1111/tran.12406
|View full text |Cite
|
Sign up to set email alerts
|

Towards a geographical account of shame: Foodbanks, austerity, and the spaces of austere affective governmentality

Abstract: This paper is about shame, its geographies, and its role in the government of conduct in austerity Britain. Drawing on ethnographic and interview data from a Trussell Trust foodbank in the Valleys of South Wales, the geography of shame is investigated through its spatiality, temporality, and politics. This paper demonstrates how shame is a central framework for understanding the contested politics of austerity both in the places it creates and through the feelings, behaviours, and values it encourages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…These ‘soft’ strategies of poverty governance, then, reconfigure economic and political subjectivities and thus are important technologies of the self (Foucault et al, 1988; Rose, 1990) through which political‐economic imperatives are realised as they are embodied. Indeed, in a recent paper, Maskovsky and Piven (2020) argue that four decades of neoliberal social and economic policy have created a ‘regime of humiliation’ in which the poor have been shamed into limited political engagement and delegitimised as political actors (see also Strong, 2021). The shaping of individual economic practices and the management of feelings are therefore central to how political possibilities are conceived, and economic rights defined.…”
Section: Locating Hope and Its Politicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These ‘soft’ strategies of poverty governance, then, reconfigure economic and political subjectivities and thus are important technologies of the self (Foucault et al, 1988; Rose, 1990) through which political‐economic imperatives are realised as they are embodied. Indeed, in a recent paper, Maskovsky and Piven (2020) argue that four decades of neoliberal social and economic policy have created a ‘regime of humiliation’ in which the poor have been shamed into limited political engagement and delegitimised as political actors (see also Strong, 2021). The shaping of individual economic practices and the management of feelings are therefore central to how political possibilities are conceived, and economic rights defined.…”
Section: Locating Hope and Its Politicsmentioning
confidence: 99%
“…In so doing, this paper provides a novel empirical contribution to the geographical literature on hope and responds to Kleist and Jansen's call for ‘a revalorization of hope as an ethnographic category in critical analysis rather than a normative banner in manifestos of optimism’ (2016, p. 374). Second, while the burgeoning literature on affect in geography has offered important insights into the lived, embodied, and felt dimensions of economic life (Cockayne, 2016; Smyth, 2021), especially as it relates to austerity (Hall, 2019; Hitchen, 2021; Stenning, 2020), only recently have the affective dimensions of social service provisioning been considered in the geographical literature (Denning, 2021; Horton, 2016; Jupp, 2021; Strong, 2021). As such, this paper advances the literature on the politics of affect (Anderson, 2012, 2017) and geographical scholarship on ‘poverty politics’ (Crane et al, 2020; Lawson & Elwood, 2014) by theorising how hope may be used as a placating force to cement existing economic arrangements and foreclose alternative political imaginaries.…”
Section: Introduction: Hope and Hardshipmentioning
confidence: 99%
“…Furthermore, because shame is framed and produced through particular spaces intertwined with the broader politics of inequality (Strong 2021), it is necessary to consider the sociospatiality that causes the experiences of these groups-residing in the same geographic location-to intersect. Thus, I investigated how Indigenous and non-Indigenous people in cities navigate welfare and the mutual obligation regime based on their cultural practices and values.…”
Section: Kanagawa Universitymentioning
confidence: 99%
“…Similarly, Mitchell and Vincent (2021), who investigated cultural differences of shame in the lived experiences of welfare recipients in cross‐cultural groups, showed that shame is culturally inflected, historically conditioned, and spatially situated; while the experiences of shame of an asylum seeker and an Anglo woman seeking basic income involved a mix of acceptance and refusal, shame was absent among many Aboriginal people in a specific area, which was subject to IM. Drawing on Strong (2021), who examined the spatiality of shame, Mitchell and Vincent (2021) viewed shame not as limited to a personal setting, but rather as inhabiting the boundary between the private and public spheres, and between the personal and collective domains; they argued that shame involved giving meaning to one's culture. Accordingly, the experience of shame is a process of cultural boundary making, entailing both a self‐definition and collective identity (Mitchell and Vincent 2021).…”
mentioning
confidence: 99%
“…The reasons are in part geographical: hunger is experienced at an intimate, bodily scale. Its association with shame and embarrassment, in a western context at least, lead to its heightened performance in private spaces away from view (Strong, 2020c). Limits to representation also trace the limits of language.…”
Section: Framing Hungermentioning
confidence: 99%